2020
DOI: 10.1097/ijg.0000000000001684
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic Artery and Superior Ophthalmic Vein Blood Flow Dynamics in Glaucoma Investigated by Phase Contrast Magnetic Resonance Imaging

Abstract: Precis: Ophthalmic artery (OA) and superior ophthalmic vein (SOV) blood flow were quantified by phase contrast magnetic resonance imaging (PC MRI) and seemed lower in glaucoma. Venous flow dynamics was different in glaucoma patients with a significantly decreased pulsatility. Introduction: Studies using color Doppler imaging and optical coherence tomography flowmetry strongly suggested that vascular changes are involved in the pathophysiology of glaucom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Other studies have reported similar results, with reduced mean and maximal flow in the OA and SOV in patients with open-angle glaucoma. Furthermore, a reduced variation of flow in the SOV has been detected in the glaucoma group, supporting the hypothesis of impaired venous outflow in these patients [152]. However, changes in blood flow rates of the OA after significant IOP reduction of in patients with ocular hypertension could not be detected [153].…”
Section: Clinical and Scientific Relevance Of Mri For Ocular And Card...mentioning
confidence: 56%
“…Other studies have reported similar results, with reduced mean and maximal flow in the OA and SOV in patients with open-angle glaucoma. Furthermore, a reduced variation of flow in the SOV has been detected in the glaucoma group, supporting the hypothesis of impaired venous outflow in these patients [152]. However, changes in blood flow rates of the OA after significant IOP reduction of in patients with ocular hypertension could not be detected [153].…”
Section: Clinical and Scientific Relevance Of Mri For Ocular And Card...mentioning
confidence: 56%